2020
DOI: 10.1016/j.landusepol.2019.104333
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to transformation towards participatory adaptation decision-making: Lessons from the Cork flood defences dispute

Abstract: This paper analyses the causes and consequences of public participation failures in flood hazards management and the important lessons they offer for climate change adaptation. Despite the potential for participatory adaptation decision-making, scholarship on adaptation has remained largely separate from the literature on participatory environmental governance. This paper brings these literatures into conversation by applying the concept of transformation to both adaptation outcomes and adaptation decision-mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The literature we identified on stakeholder engagement conveys the need for the political system to undergo deep institutional transformation towards more inclusive forms of policy development and implementation with those directly invested or affected by specific policies [ 80 ]. In our review we found that the emergence of opposition groups such as Save Cork City, the Clontarf Residents Coalition, and the Skibbereen Flood Forum, objecting to local flood defense strategies, exemplify the growing discontent of flood impacted communities with state organisations such as the Office of Public Works 1 (OPW).…”
Section: Integrated Overview Of Approaches To Change In Ireland Using the Three Spheres Of Transformation Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature we identified on stakeholder engagement conveys the need for the political system to undergo deep institutional transformation towards more inclusive forms of policy development and implementation with those directly invested or affected by specific policies [ 80 ]. In our review we found that the emergence of opposition groups such as Save Cork City, the Clontarf Residents Coalition, and the Skibbereen Flood Forum, objecting to local flood defense strategies, exemplify the growing discontent of flood impacted communities with state organisations such as the Office of Public Works 1 (OPW).…”
Section: Integrated Overview Of Approaches To Change In Ireland Using the Three Spheres Of Transformation Frameworkmentioning
confidence: 99%
“…Events, which are arguably set with the sole purpose of meeting EU Flood Directive requirements for public engagement, are tokenistic and counterproductive. Failure to recognize stakeholder inputs more widely in this instance has led to a significant and costly impasse in the development and implementation of much needed flood management solutions [ 80 ]. It has also led to mismatched expectations concerning the role that the state plays in providing protection and support to impacted communities, suggesting a critical need for a new ‘social contract’, which more clearly defines the role both the state and communities should play in new processes of climate adaptation [ 82 ].…”
Section: Integrated Overview Of Approaches To Change In Ireland Using the Three Spheres Of Transformation Frameworkmentioning
confidence: 99%
“…Lorenzoni et al [21] identify barriers that operate at individual and social levels and call for targeted and tailored information provision. Jeffers [87] argues for a wider change in hazard management policy and resourcing for more effective public participation in hazard management and climate change adaptation. Wamsler et al [81] suggest that under current structures and mechanisms, public engagement hinders sustainable outcomes and call for explicit support and systematic mainstreaming of public engagement to support sustainability.…”
Section: Barriers To Public Participation In Climate Changementioning
confidence: 99%
“…Hügel and Davies' [89] recent review found that lack of trust affects citizens' willingness to get involved in climate change adaptation. Lack of trust could stem from different factors such as experiencing unsuccessful public participation trials by major governance bodies [87]. The formation of distrust could immediately result in lack of citizens' willingness for future engagement.…”
Section: Barriers To Public Participation In Climate Changementioning
confidence: 99%
“…From the early modern period the expansion of the city was facilitated by the culverting and redirection of the river, but the largest human interference was in the construction of two hydroelectric dams in the 1950s which flooded extensive areas up-stream, including most of a submerged glacial woodland, called the Gearagh (McCarthy 2006; see Figure 2). In recent years, a proposed flood defence plan has brought renewed attention on the river and its role within the region, and has highlighted the need for greater public participation in decisionmaking around significant landscape features (English 2019;Jeffers 2020).…”
Section: Introductionmentioning
confidence: 99%